Intracellular production of IFN-alpha 2b in Lactococcus lactis - Bayat, Omid; Baradaran, Ali; Ariff, Arbakariya; Mohamad, Rosfarizan; Abdul Rahim, Raha (Springer Netherlands, 2014)
Human interferon alpha (IFN-α) was expressed in two strains of Lactococcus lactis by aid of two promoters (P32 and Pnis) giving rise to two recombinant strains: MG:IFN and NZ:IFN, respectively. The expression of IFN was confirmed by ELISA and western blotting. Highest production was achieved using glucose for growth of both recombinant strains with nisin, used for induction of the recombinant strain with Pnis promoter, at 30 ng/ml. The optimum time for MG:IFN was 9 h and for NZ:IFN was 4.5 h. The highest productions by MG:IFN and NZ:IFN were 1.9 and 2.4 μg IFN/l, respectively. Both of the expressed IFNs showed bioactivities of 1.9 × 10(6) IU/mg that were acceptable for further clinical studies.